The limitations of epicardial mapping as a guide to the surgical therapy of ventricular tachycardia. - Scott R. Spielman; Eric L. Michelson; Leonard N. Horowitz; J F Spear; E N Moore (1978)
The adequacy of intraoperative epicardial mapping as a guide to surgical procedures performed to terminate ventricular arrhythmias was investigated. Ligation of the anterior septal or left anterior descending coronary artery in 28 dogs produced ventricular arrhythmias that were studied 24-36 hours following occlusion. The sites of origin of 26 tachycardias were determined to be in the subendocardium by using extensive epicardial, endocardial and intramural mapping techniques and were verified by demonstrating unaltered activation sequences during pacing from these earliest sites. Epicardial breakthrough followed earliest directly recordable ventricular activity by as little as 7 msec. Without endocardial mapping many of these tachycardias would have been incorrectly identified as originating in the fascicles or epicardium. The sites of epicardial breakthrough were anatomically distant from the sites of origin by a markedly varying extent (5mm to 6cm). Two rhythms might be close in their sites of earliest epicardial appearance yet distant on the endocardium or vice versa. We conclude that epicardial mapping may not be sufficient to identify or predict the origins of many ventricular tachycardias and that the success of surgery to abolish these arrhythmias may be enhanced by preoperative and intraoperative endocardial mapping.